Efficacy and safety of early chest tube removal after selective pulmonary resection with high-output drainage: A systematic review and meta-analysis. Issue 12 (24th March 2023) - Zhu, Junwei; Xia, Xueyang; Li, Rongyao; Song, Weikang; Zhang, Zhiqiang; Lu, Huawei; Li, Zhiwei; Guo, Qingwei
Abstract : Background: There is controversy over the drainage threshold for removal of chest tubes in the absence of significant air leakage after selective pulmonary resection. Methods: A comprehensive search of online databases (PubMed, Web of Science, Embase, Cochrane Library, Scopus, Ovid, Elsevier, Ebsco, and Wiley) and clinical trial registries (WHO-ICTRP and ClinicalTrials.gov) was performed to investigate the efficacy and safety of early chest tube removal with high-output drainage. Primary outcome (postoperative hospital day) and secondary outcomes (30-day complications, rate of thoracentesis, and chest tube placement) were extracted and synthesized. Subgroup analysis, meta-regression, and sensitivity analysis were used to explore the potential heterogeneity. Study quality was assessed with the Newcastle-Ottawa Scale, and evidence was graded using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) assessment by the online GRADEpro Guideline Development Tool. Results: Six cohort studies with a total of 1262 patients were included in the final analysis. The postoperative hospital stay in the high-output group was significantly shorter than in the conventional treatment group (weighted mean difference: −1.34 [−2.34 to −0.34] day, P = .009). While there was no significant difference between 2 groups in 30-day complications (relative ratio [RR]: 0.92 [0.77–1.11], P = .38), the rate of thoracentesis (RR: 1.93 [0.63–5.88], P = .25) and the rate of chest tube placement (RR: 1.00 [0.37–2.70], P = .99). According to the sensitivity analysis, the relative impacts of the 2 groups had already stabilized. Subgroup analysis revealed that postoperative hospital stay was modified by Newcastle-Ottawa Scale score. The online GRADEpro Guideline Development Tool presented very low quality of evidence for the available data. Conclusions: This meta-analysis revealed that it is feasible and safe to remove a chest tube with high-output drainage after pulmonary resection for selected patients.